2018
DOI: 10.1002/rnc.4364
|View full text |Cite
|
Sign up to set email alerts
|

Sign‐consensus over cooperative‐antagonistic networks with switching topologies

Abstract: Summary This paper studies sign consensus, a collective behavior of multiagent systems, when both cooperative and antagonistic interactions coexist among agents. By sign consensus, it means that the states of all agents will eventually achieve the same sign but may with different magnitudes. Compared with some recent works on sign‐consensus problems, where only fixed graphs are considered and the graph adjacency matrix needs to be eventually positive, this paper allows the graph to be switching over time. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…This phenomena for general linear multiagent systems is called sign‐consensus in Reference , where the signed graph is fixed and eventually positive. Very recently, sign‐consensus problem of homogeneous multiagent systems is investigated over switching signed graphs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomena for general linear multiagent systems is called sign‐consensus in Reference , where the signed graph is fixed and eventually positive. Very recently, sign‐consensus problem of homogeneous multiagent systems is investigated over switching signed graphs …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, sign-consensus problem of homogeneous multiagent systems is investigated over switching signed graphs. 23,24 Although homogeneity of system dynamics may ease the theoretical analysis, in practice, all multiagent systems are inherently heterogenous, that is, all agents may have different dynamics. For example, two robots are hardly identical in every aspect.…”
mentioning
confidence: 99%
“…In fact, studies on structurally unbalanced signed digraph have already been reported in [14,15,[19][20][21][22][23][24], etc. In [14,15], agents converge to zero in mean square under arbitrary initial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the pioneering work [23], it is shown that, for the linear timeinvariant (LTI) MASs, if the graph adjacency matrix is eventually positive, sign-consensus is achieved under a state feedback sign-consensus protocol and a fully distributed sign-consensus protocol, respectively. e xed signed digraph in [23] is extended in [24] to being switched over time. Sign-consensus protocols are proposed for three types of time-varying graphs, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation